Posisi Pasar Karet Indonesia Di Pasar Internasional - Nurzakiah, Sitty; Rifin, Amzul; Nurmalina, Rita (Forum Agribisnis, 2024)
Indonesia's position as the largest rubber producing country in the world allows them to become the main exporter of natural rubber. Indonesia exports the majority of its natural rubber production to countries like Japan, India, Brazil, the United States, South Korea, China, Turkey, and others. The competition between Indonesia and other producing countries in exporting rubbers to international markets is relatively tight. The aim of this research is to analyze the position of Indonesia’s technically specified natural rubbers (TSNR) in the international market compared to other exporting countries. The analytical method used is the Almost Ideal Demand System (AIDS) Model. The data used in this research is secondary data from Indonesia, Thailand, Malaysia, Ivory Coast, Vietnam, Belgium, and Nigeria over the last 10 years (2012 – 2022). The results show that there is a tight competition between Indonesia and Thailand, Ivory Coast, Belgium, Nigeria and the Rest of the World in competing for market share of natural rubber in the international market because the relationship between Indonesia's natural rubber and these countries are substitutional. Meanwhile, Indonesia's natural rubber relationship with Malaysia is complementary. Indonesian natural rubber is a normal good, so if there is an increase in prices it will cause a decrease in demand. If there is an increase in demand for rubber exports in the international market, then the country that will benefit the most is Vietnam. Meanwhile, Indonesia is the fourth ranked country that will benefit the most if it happens.